Comparative Test Circuit Training To Increase Leg Muscle Strength - I Putu Prisa Jaya; I Putu Astrawan (Jurnal EduHealth, 2023)
Improving physical condition at the Futsal UKM Universitas Bali International, training was carried out on the Calf Raise Diagonal Cone Hop circuit  and the Front Cone Hop Squad circuit. This study aims to determine the training of the Calf Raise Diagonal Cone Hop circuit  and the Squad Front Cone Hop circuit in increasing leg muscle strength. The research method used is the randomized pre and post test group design experimental method. The research sample was 30 Futsal UKM participants who were divided into 2 groups, each group consisting of 15 people. Kelompok I diberikan pelatihan sirkuit Calf Raise Diagonal Cone Hop, sedangkan kelompok II diberikan pelatihan  Squad Front Cone Hop. Frequency of exercise 3 times a week for 6 weeks. Leg muscle strength is measured with a leg dynamometer. The results of the test study were different from the non-parametric U Mann-Whitney test in group I after treatment obtained an average leg muscle strength of 133.00 ± 26.43 kg. While the results of group II after treatment obtained an average leg muscle strength of 11 6.33 ± 1 4.76 kg. The difference in average leg muscle strength between before and after training from the two groups obtained a value of p = 0.000 which means there is a significant difference with a percentage increase in group I of 18.04% and group II of 13.26%. Based on the results of the study, it can be concluded that these two forms of training can be used to increase leg muscle strength. However, Calf Raise Diagonal Cone Hop circuit training  is more effective than the Squad Front Cone Hop circuit to increase leg muscle strength.